Synthesis of Thiazolidinone-Thiadiazole Hybrids: Molecular Docking and Antimicrobial Evaluation - Taher, Salam Gh. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
A green synthesis of bis-thiazolidinone-thiadiazole hybrids (6a-h) exhibiting mild to potent antibacterial activity is reported. The hybrid compounds were synthesized in one-pot three-component Microwave-assisted reaction under solvent free condition from the corresponding bis- thiadiazole amines (3) reaction with various aldehydes, and thioglycolic acid. The products were obtained in acceptable yields and characterized based on spectroscopic techniques (Fourier transform infrared, proton nuclear magnetic resonance, carbon-13 nuclear magnetic resonance, and carbon-attached proton test nuclear magnetic resonance). Antibacterial screening was performed on the synthesized compounds (6a-h) against both Grampositive strains (Staphylococcus and Streptococcus) and Gramnegative strains (Escherichia coli and Klebsiella pneumoniae), with their efficacy compared to the reference antibiotics ciprofloxacin and vancomycin. Overall, the synthesized compounds demonstrated highly antibacterial properties. Among the series, compounds (6b, 6d, and 6e) exhibited broad-spectrum and potent levels of antibacterial activity against species; furthermore, they showed notable activity against K. pneumoniae as the most antibacterial-resistant pathogen. The result of Molecular docking studies indicated that OH, OCH3 substituents, such as in compounds (6b), enhanced binding ability interaction and producing conventional hydrogen bond with the minimum energy affinity ( ∆G).